Blimp1+ cells generate functional mouse sebaceous gland organoids in vitro - Alona Feldman; Dzmitry Mukha; Itzhak I. Maor; Egor Sedov; Elle Koren; Yahav Yosefzon; Tomer Shlomi; Yaron Fuchs (Nature Communications, 2019)
The sebaceous gland (SG) has been proposed to be replenished by pools of cells, including a population in the SG base, marked by Blimp1. Here, the authors show that Blimp1+ cells can establish an organoid model of the SG, which is regulated by c-Myc and can recapitulate the early stages of acne vulgaris.